Development and Functional Evaluation of an Upper Extremity Rehabilitation System Based on Inertial Sensors and Virtual Reality - Je-Nam Kim; Mun-Ho Ryu; Ho-Rim Choi; Yoon-Seok Yang; Tae-Koon Kim (International Journal of Distributed Sensor Networks)
An extremity rehabilitation program was proposed based on inertial measurement units (IMU) and virtual reality. A single IMU consists of a three-axis accelerometer, gyroscope, and geomagnetic sensors. One IMU is attached to the upper arm (master) and another to the forearm (slave). The IMUs are connected using a distributed sensor network implemented with interintegrated circuit communication. The motion-tracking algorithm running on a PC tracks the subject's hand based on the estimated IMU orientation and segment lengths through forward kinematics. The training contents, including various dynamic movements and static holds, were designed to evaluate the spatiotemporal aspects of the subject's functionality. The system was tested on a group of healthy subjects and a group with a simulated stiff elbow, allowing the evaluations to be quantitatively differentiated. The stiff elbow was simulated by taping the elbow to restrict the range of elbow motion. We expect the patients to be able to assess their own status without assistance from a therapist and select appropriate training methods to increase their rehabilitation effectiveness. Future studies will verify the availability and reliability of the upper extremity rehabilitation program for patients with a hemiplegia, leading to the development of an upper extremity rehabilitation program for three-dimensional movements of the upper extremities.